DYSAUTONOMIA FOLLOWING ACUTE ISCHEMIC STROKES: A SINGLE INSTITUTIONAL EXPERIENCE - Shekhbzeni, Aso Sabir (Journal of Sulaimani Medical College, 2022)
Background Many studies have found that patients with ischemic stroke can develop autonomic system disturbances, affecting the heart, causing different types of arrhythmias and even sudden death. Objectives To analyze the occurrence of cardiovascular autonomic dysfunction and cardiac arrhythmias after acute ischemic stroke. Patients and Methods This case-controlled study was conducted at the Rizgary Teaching Hospital from July 1st, 2018, to September 30th, 2019. Fifty patients with acute ischemic stroke were enrolled consecutively and were age-matched and gender-matched with a group of 50 individuals (control group). Four bedside autonomic function tests (deep breathing, heart rate response to standing, isometric handgrip test, and blood pressure response to standing) were used to assess autonomic dysfunction during the acute post-stroke phase. In addition, all patients and controls underwent 24-hour Holter cardiac monitoring. Results Although abnormal autonomic function testing was more frequent in post-stroke cases than in healthy controls, there was no statistically significant difference in these results among stroke sub-groups. There were more arrhythmias in patients with stroke in comparison with the control group; premature ventricular and atrial contractions were more frequent in stroke patients than in the control group (P-value <0.001 and P-value<0.001, respectively). Conclusion Cardiac dysautonomia is common in patients with acute ischemic stroke, and cardiac dysrhythmias are commonly encountered in patients with insular infarctions. Whether these dysrhythmias are life-threatening or not, further analytic studies are required to uncover their clinical significance.
Keywords: Ischemic stroke; Arrhythmia; Autonomic function tests; Dysautonomia